Functionality Of Religious Education In The Development Of The Sense Of Self-Worth - Handan Yalvaç Arıcı (Artuklu Akademi, 2022)
The feeling of self-worth is an important emotion that supports individuals to accept themselves and their abilities, to value and be realistic about themselves. Today, the lives presented in traditional media and social media and the envy for those lives are increasing, and especially the beauty standards, wealthy lives, positions, prestiges revealed by influencers on social media lead individuals to compare their own lives with those lives and deprive their individual originality and freedom. People who base their self-worth on external sources such as physical appearance, academic success, wealth and prestige cannot protect their inner integrity and can become depressed. On the other hand, it is known that people who take their self-worth from their inner resources live more peacefully, do not see themselves as worthless in negative situations and focus on solving problems in negative situations. Studies show that when the sense of self-worth is built well, individuals are more objective and understanding towards themselves and solve problems more easily. Religious education guides individuals to plan their world and afterlife and to well use what they have innately. In this study, self-worth, virtualization and construction of self-worth, the functionality of religious education in constructing self-worth is explained.